Developmental and maintenance defects in Rett syndrome neurons identified by a new mouse staging system in vitro - Baj, Gabriele; Patrizio, Angela; Montalbano, Alberto; Sciancalepore, Marina; Tongiorgi, Enrico (Frontiers in Cellular Neuroscience, 2014)
Rett Syndrome (RTT) is a neurodevelopmental disorder associated with intellectual disability, mainly caused by loss-of-function mutations in the MECP2 gene. RTT brains display decreased neuronal size and dendritic arborisation possibly caused by either a developmental failure or a deficit in the maintenance of dendritic arbour structure. To distinguish between these two hypotheses, the development of Mecp2-knockout mouse hippocampal neurons was analyzed in vitro. Since a staging system for the in vitro development of mouse neurons was lacking, mouse and rat hippocampal neurons development was compared between 1-15 days in vitro (DIV) leading to a 6-stage model for both species. Mecp2-knockout hippocampal neurons displayed reduced growth of dendritic branches from stage 4 (DIV4) onwards. At stages 5-6 (DIV9-15), synapse number was lowered in Mecp2-knockout neurons, suggesting increased synapse elimination. These results point to both a developmental and a maintenance setback affecting the final shape and function of neurons in RTT.